Role and Development of Digital Agriculture in Uzbekistan - N.A. Ashurmetova; A.U. Mynbaeva; M.F. Ibrahimova (Zien Journals, 2023)
Digital technologies in agriculture are the automation of technological agricultural processes through digital modeling of all production cycles. The penetration of digital technologies into the field of agricultural work is increasing every year. The main reasons for this are the need to reduce production costs and increase the productivity of the agricultural sector.
Keywords: agriculture; precision farming technologies; digital technologies